Pregnancy rates in heifers and suckled beef cows after synchronized ovulation using PGF2", GnRH, and norgestomet - Hoffman, D.P.; Stevenson, Jeffrey S.; Krehbiel, C.L.; Nichols, David A.; McKee, R.M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Suckled cows and virgin heifers received a novel treatment that included PGF 2", GnRH, and norgestomet, with the objective of inducing estrus in prepubertal heifers and anestrous suckled cows, as well as synchronizing ovulation in estrus-cycling females. The treatment consisted of two injections of PGF 2" (day 14 and 0) plus 100 Fg of GnRH and a 6-mg norgestomet ear implant on day 7. The implant was removed 24 h after the second injection of PGF2" (day 0), and a second injection of GnRH was given 30 hours after implant removal. The treated females were inseminated 18 hours after the second injection of GnRH or at estrus, if it was detected before the second GnRH injection. Pregnancy rate in the treated females was greater than in control females that had received two injections of PGF 2" 14 days apart and were inseminated at estrus or at one fixed time (60.2 vs. 48%). The treatment successfully induced a fertile ovulation in previously prepubertal heifers and anestrous cows, resulting in 63.5% pregnancies vs. 26.5% for controls. In addition, in females not showing estrus, the treatment increased pregnancy rate following a fixed-time insemination (treatment vs. control; 60.0 vs. 3.8%). We concluded that treatment with PGF2", GnRH, and norgestomet induced estrus and increased pregnancy rates in prepubertal heifers, anestrous cows, and cycling females.
Keywords: Beef; GnRH; Norgestomet; PGF2; Heat synchronization; Prepubertal heifers; Anestrous suckled cows